1998
DOI: 10.1021/ic980323k
|View full text |Cite
|
Sign up to set email alerts
|

A Steeply Pyramidal Silylamine:  N,O-Dimethyl-N-silylhydroxylamine

Abstract: N,O-Dimethyl-N-silylhydroxylamine (H(3)SiMeNOMe) has been prepared by reaction of HMeNOMe with H(3)SiBr and 2,6-lutidine as an auxiliary base. Its identity has been proved by gas-phase IR and solution NMR spectroscopy of the nuclei (1)H, (13)C, (15)N, (17)O, and (29)Si and by mass spectrometry. The solution NMR data indicate aggregation of the compound in solution. H(3)SiMeNOMe decomposes within weeks at ambient temperature, and an extrusion of methylnitrene is probably the mechanistic pathway involved. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…For the OH- and F-substituted compounds, both of which have higher electronegativity than nitrogen, the fluorine atom and the hydroxyl group have negative partial charges, resulting in an electrostatic attraction with the silyl group and net stabilization of the pyramidal geometry. The computed θ t angle of 336° for HN(OH)SiH 3 is in good accord with the experimental value of 332.3° for N(CH 3 )(SiH 3 )(OCH 3 ) 4 Computed θ τ (deg) and the NPA Partial Charges for Substituted Silylamines (NHXSiH 3 ) at the HF/6-31G(d) and MP2/6-311G(dp) Levels HF/6-31G(d)MP2/6-311G(dp)Xθ t q (X) a θ t q (X) a SiH 3 360.0 0.5909 359.8 0.5749 PH 2 360.0 0.4630 360.0 0.4440 SH 359.8 0.3075 359.6 0.2893 NH 2 357.2 0.0242 352.5 0.0184 CH 3 355.7 0.2057 351.5 0.1981 H 352.2 0.4092 349.1 0.3784 Cl 345.7 0.1031 342.9 0.0948 OH 335.7 −0.1451 332.8 −0.1443 F 329.2 −0.3061 327.9 −0.3167 a Partial charges range from 0.39 to 0.43 e on the hydrogen attached to nitrogen and from 0.56 to 0.60 e on the silyl group for all compounds. …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…For the OH- and F-substituted compounds, both of which have higher electronegativity than nitrogen, the fluorine atom and the hydroxyl group have negative partial charges, resulting in an electrostatic attraction with the silyl group and net stabilization of the pyramidal geometry. The computed θ t angle of 336° for HN(OH)SiH 3 is in good accord with the experimental value of 332.3° for N(CH 3 )(SiH 3 )(OCH 3 ) 4 Computed θ τ (deg) and the NPA Partial Charges for Substituted Silylamines (NHXSiH 3 ) at the HF/6-31G(d) and MP2/6-311G(dp) Levels HF/6-31G(d)MP2/6-311G(dp)Xθ t q (X) a θ t q (X) a SiH 3 360.0 0.5909 359.8 0.5749 PH 2 360.0 0.4630 360.0 0.4440 SH 359.8 0.3075 359.6 0.2893 NH 2 357.2 0.0242 352.5 0.0184 CH 3 355.7 0.2057 351.5 0.1981 H 352.2 0.4092 349.1 0.3784 Cl 345.7 0.1031 342.9 0.0948 OH 335.7 −0.1451 332.8 −0.1443 F 329.2 −0.3061 327.9 −0.3167 a Partial charges range from 0.39 to 0.43 e on the hydrogen attached to nitrogen and from 0.56 to 0.60 e on the silyl group for all compounds. …”
Section: Resultssupporting
confidence: 81%
“…To corroborate recent theoretical findings that d orbitals play a minor role in bonding for main group elements, Schleyer and co-workers 7 proposed that the n→σ XH * negative hyperconjugation effect may be responsible for the difference between the physical and structural properties of first- and second-row elements. In other studies, it has been suggested 1c, that the planarity may be caused by the electrostatic repulsion among the silyl groups since the Si−N bond is more polar than the C−N bond.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The observation was ascribed to the influence of the high electronegativity of the alkoxy substituent bound to the nitrogen atom which causes a high barrier to inversion, thus overcoming the counter influence of the silicon substituent. Examples are provided by (H 3 Si) 2 NOMe 5 and (H 3 Si)MeNOMe 6 which have slightly and steeply pyramidal cores respectively.…”
Section: Introductionmentioning
confidence: 99%